(untitled) (American Journal of Islam and Society, 2006)
Pnina Werbner’s Pilgrims of Love, a truly exceptional book in several important ways, is the result of some eleven years of fieldwork in Britain and Pakistan. While the topic, understanding a transnational Sufi cult, is quite conventional within the discipline of anthropology, the time span in which the research was conceived and conducted is perhaps one wherein anthropology began to question seriously even its most taken-for-granted truths. This makes the final product anything but conventional. The author makes very clear her position as an anthropologist and the difficulties she experienced as a western Jewish female academic writing about a Pakistani, or second-generation Pakistani, predominantly Muslim male practitioner’s perspective. Her honesty about the nature of her field experience, the classic nature of the research itself within the canon of anthropological literature, and her assessment of what she calls “the limits of postmodern anthropology” (pp. 14-15, 291-302) add a certain depth of substance to the discipline’s ongoing discussion of the subject-object relationship. This text is an important contribution to the body of literature within the anthropology of religion and Islam, comparative studies of Islamic movements, transnationalism, and, in general, to students and scholars of Pakistan and South Asia ...